2011
DOI: 10.1021/nn202786g
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic Performance of Ultrasmall PbSe Quantum Dots

Abstract: We investigated the effect of PbSe quantum dot size on the performance of Schottky solar cells made in an ITO/PEDOT/PbSe/aluminum structure, varying the PbSe nanoparticle diameter from 1 to 3 nm. In this highly confined regime, we find that the larger particle bandgap can lead to higher open-circuit voltages (∼0.6 V), and thus an increase in overall efficiency compared to previously reported devices of this structure. To carry out this study, we modified existing synthesis methods to obtain ultrasmall PbSe nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
222
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 221 publications
(228 citation statements)
references
References 44 publications
4
222
0
2
Order By: Relevance
“…Films of initially well-dispersed quantum dots with a mean interparticle spacing of roughly 15 Å undergo a contraction to ∼2À3 Å upon exchange with methoxide. We note a similar effect reported in PbSe nanoparticle films where hydrous methanol was used to replace Pb(oleate) 2 . 15 In that work, partial fusion of nanoparticles was reported upon ligand exchange, which we do not observe with the treatment presented here.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…Films of initially well-dispersed quantum dots with a mean interparticle spacing of roughly 15 Å undergo a contraction to ∼2À3 Å upon exchange with methoxide. We note a similar effect reported in PbSe nanoparticle films where hydrous methanol was used to replace Pb(oleate) 2 . 15 In that work, partial fusion of nanoparticles was reported upon ligand exchange, which we do not observe with the treatment presented here.…”
Section: Resultssupporting
confidence: 82%
“…Previous studies using carboxylic acids and PbSe have found similar quick reversals of excitonic red shift upon air exposure. 13 We demonstrate the reduction of interparticle spacing upon ligand exchange from Pb(oleate) 2 to Pb(MeO) 2 by a comparative TEM study in Figure 4. Films of initially well-dispersed quantum dots with a mean interparticle spacing of roughly 15 Å undergo a contraction to ∼2À3 Å upon exchange with methoxide.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations